2002
DOI: 10.1046/j.1470-6431.2002.t01-1-00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Swedish preschool children's experience of food

Abstract: Focus group interviews were carried out at 12 preschools. The aim was to investigate children's perceptions and experiences of food, and the possibility of using focus group techniques with children aged 3–5 years. A total of 103 children participated. The children associated food and eating with rules and norms. Most children described these rules and norms as well as what they were and were not allowed to do. They knew very well the difference between acceptable and non‐acceptable mealtime behaviour, and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[11][12][13] In this specific part of the study, a qualitative approach based on Grounded Theory with interviews was chosen. [11][12][13] In this specific part of the study, a qualitative approach based on Grounded Theory with interviews was chosen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] In this specific part of the study, a qualitative approach based on Grounded Theory with interviews was chosen. [11][12][13] In this specific part of the study, a qualitative approach based on Grounded Theory with interviews was chosen.…”
Section: Methodsmentioning
confidence: 99%
“…This study was carried out in 1998 as part of a larger investigation of pre-school children's food habits, in which both qualitative and quantitative methods were used. [11][12][13] In this specific part of the study, a qualitative approach based on Grounded Theory with interviews was chosen. 14 Thirty-four interviews with pre-school staff from 12 different schools were conducted during pre-school hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the theory to diet, it is easy to imagine when contextual factors such as price of available food, hunger pangs, habits or time constraints could override attitudes towards healthy eating and dominate in situ food choices. The influence of context can be seen in the studies by Wesslén et al (2002) and Mattsson and Helmersson (2007), who show that Swedish youth desire healthy eating and view fast food as unhealthy, but these attitudes are prevented from translating directly into behaviour because of the stronger intervening influences of familial relations, price and convenience. Thus, ABC theory predicts that attitudes towards healthy eating would only correspond with behaviour when the context in which food choices are made supports healthy eating habits.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…When examining preschool children's food habits and meal situation, it was shown that the energy and nutrient intakes of food at the preschool were lower than recommended, although this was compensated for by meals eaten at home (27). It was also shown that preschool children associated food and meals with rules and norms, and that at this age they had not yet begun to categorize food into good or bad food, but instead into food and non-food.…”
Section: Meal Research As a New Academic Disciplinementioning
confidence: 99%